A Large Gastric Trichobezoar in a Teenage Girl : A Case Report (TAJ: Journal of Teachers Association, 2018)
Bezoars are retained concretions of foreign materials or indigestible organic substances in the digestive tract resulting of their ingestion and accumulation, involving mainly the gastric lumen. The incidence of gastric bezoars is very low and they are of varied composition. We report a case of gastric trichobezoar in a 13- year old young girl who presented with intermittent pain in her epigastrium with dyspepsia. Her parents gave the history of intermittent ingestion of hairs since 06 years of age. The patient was relatively healthy with no history of psychiatric disorder or gastric surgery. She was investigated with ultrasound of abdomen, barium meal study and computed tomography followed by endoscopy which revealed gastric trichobezoar. The patient underwent gastrotomy which revealed a large trichobezoar confirming our radiological diagnosis. The mode of presentation and appearance on various imaging modalities like ultrasound, barium meal and computed tomography are discussed.TAJ 2012; 25: 77-80